Doris Howes Calloway: An Exemplary Administrator and Leader. Issue 2 (March 2023) - King, Janet C.; Yates, Allison A.; Butte, Nancy F.; Murphy, Suzanne P.; Kretsch, Molly J.; Blackburn, Mary L.
Abstract : During her career of over 40 years, Dr Doris Calloway held a variety of leadership/administrative positions while conducting groundbreaking research in human nutrition. In those positions, she illustrated the characteristics of dynamic, successful leaders. She led change in the nutritional sciences program at the University of California, Berkeley; she valued and prioritize personal development while prioritizing the development of others; and she practiced and encouraged strategic thinking, innovation, and action while being honest and ethical. Plus, she communicated effectively across cultures.